(untitled) (Fiep Bulletin - online, 2015)
The general theme of the world congress of physical and sportive education organized by the FFGEGV, under the international patronage of the FIEP, is of the greatest interest. Its theoretical and practical importance derives, also, from the fact that it obliges one to make a synthesis of fundamental notion of divers kinds essential factor of all teaching: the lesson.